(untitled) (Baghdad Science Journal, 2012)
Background :Alkaline phosphatase (ALP) was a widely used marker for skeletal and hepatobiliary disorders, but its activity was also increased in atherosclerosis and peripheral vascular disease. Several study has showed that ALP activity was increased in the sera of diabetic patients. The current study was conducted to evaluate ALP activity in type 2 diabetic patients and optimum conditions for enzyme activity in their sera.Methods: This study was carried out at in AL-Yarmok hospital(diabetic center) between February /2009 and April /2009. Fifty two patients with type 2 diabetes have been enrolled. Besides BMI, WHR, serum fasting blood glucose, ALP, HbA1C,uric acid and lipid profile levels have been performed .The relationship between ALP and other biochemical factors have been studied.Results: From a total 52 cases, FBG, HbA1C and ALP were significantly elevated P value < 0.01 while Uric acid, Cholesterol, TG, HDL, LDL,VLDL and LDL/HDL were significantly different P value < 0.05 in diabetic patients when compared with that found in control group . ALP was significantly associated with LDL (P < 0.05) and significantly negative correlation with HbA1C (P